PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSET (ROA) PADA PT SURYA TOTO INDONESIA TBK PERIODE 2013-2022 - Eva Novita; Tri Sulistyani (Journal of Research and Publication Innovation, 2024)
This study aims to examine the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Assets (ROA) in PT. Surya Toto Indonesia Tbk for the 2013-2022 period, both partially and simultaneously. The research method used is quantitative with associative methods. Data analysis techniques include descriptive statistical test, classical assumption test, correlation coefficient analysis, multiple linear regression analysis, t-test, F-test, and determination coefficient test. The results of the study show that partially, the Current Ratio has a negative and significant effect on Return On Assets. Meanwhile, the Debt to Equity Ratio partially has a negative and significant effect on Return On Assets. However, simultaneously, the Current Ratio and Debt to Equity Ratio have a positive and significant effect on Return on Assets. Based on the determination coefficient test, the Current Ratio and Debt to Equity Ratio contributed 80.6% to the Return on Assets, while the remaining 19.4% was influenced by other factors outside the research model.